French contribution to develop Prussian blue. (November 2014) - Besse Bardot, Isabelle; Bardot, Sebastien; Menetrier, Florence; Leiterer, Alexandra; Pech, Annick
Abstract Purpose: Prussian blue is an antidote indicated for the treatment of internal cesium radioisotope contamination. The French armed forces develop and manufacture some antidotal drugs meeting regulatory, analytical and pharmaceutical requirements in order to submit marketing authorization documentation. Prior to an initial meeting with the French National Agency for Medicines and Health Products Safety (ANSM) in 2011, the authors were following regulatory developments in free cyanide release, active pharmaceutical ingredient (API) synthesis, API specifications, ability of cesium/Prussian blue binding products and collection of pre-clinical data. Materials and methods: Free cyanide release was assessed by ultraviolet-visible (UV-Vis) spectrometry at 615 nm. The kinetics of cesium were evaluated in vitro by flame atomic absorption. Good laboratory practice (GLP) and mutagenic assays were examined in rat studies to assess 'no absorption'. Results: A validated method makes it possible to assess the free cyanide in API according to the published tolerability in humans. The French synthesizer meets good manufacturing practice (GMP) to give a drug that is compliant with all specifications, ensuring its high quality. Two standard mutagenic assays showed mutagenic potential, leading to further tests to obtain more information on any induced chromosomal aberrations. Absorption could be an important factor in determining the risk posed by the drug. Conclusion: The French health service provides the country with several antidotal drugs reducing Chemical, Biological, Radiological and Nuclear (CBRN) risks. Using their GMP manufacturing facilities and pharmaceutical expertise, the French armed forces have contributed to developing drugs with marketing authorization, such as pentetate calcium trisodium (Ca-DTPA) for infusion, or under development with the French Alternative Energies and Atomic Energy Commission (CEA), such as Ca-DTPA by inhalation.